2004
DOI: 10.1038/sj.bjc.6601847
|View full text |Cite
|
Sign up to set email alerts
|

Bladder cancer: worse survival in women from deprived areas

Abstract: In a case-note review of 120 women and 227 men presenting with muscle-invasive bladder tumours in 1998, survival was worse for women in 3 years of follow-up, with the greatest difference, of 19.9%, at 6 months. For more deprived women, 6-month survival was 52.3%, and 32 (37.2%) presented with advanced disease, compared with 73.5%, and three (8.8%) for less deprived women. Bladder cancer is the only common cancer for which women have worse prognosis than men as reported in the UK, continental Europe and North A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 5 publications
3
6
2
Order By: Relevance
“…Research has highlighted a synergistic association of female sex combined with higher deprivation and lower treatment use [20]. However, in the present study the interaction between deprivation and sex was not significant.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…Research has highlighted a synergistic association of female sex combined with higher deprivation and lower treatment use [20]. However, in the present study the interaction between deprivation and sex was not significant.…”
Section: Discussioncontrasting
confidence: 96%
“…We detected a significant though small gender gap in radiotherapy use. Like previous investigators [20,[22][23][24] we found that women with bladder UCC tend to present at a more advanced stage, but gender differences in radiotherapy use persisted even when the analysis was adjusted for stage. Therefore, factors other than stage must be responsible and should be explored in future research.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, the difference reduced after six months. [20] According to WHO, the survival accumulation at the end of five years in Thai females and males suffering from the bladder cancer has been equal to 39 and 61.5% respectively. Nevertheless, the survival accumulation at the end of five years in female and male patients from Madras, India has been reported as 15 and 25% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing body of knowledge that has highlighted the association of poorer outcomes with socioeconomic status and increased mortality from various cancers [2,3]. In bladder UC, several studies have shown some form of survival disparity from bladder UC associated with SES [1,[4][5][6][7][8][9][10]. Most of these studies had the primary endpoint of all-cause mortality, a measure that may be associated with SES regardless of the diagnosis of bladder cancer.…”
Section: Introductionmentioning
confidence: 99%